2020
DOI: 10.1111/jvh.13344
|View full text |Cite
|
Sign up to set email alerts
|

Altered faecal microbiota on the expression of Th cells responses in the exacerbation of patients with hepatitis E infection

Abstract: Fulminant hepatitis E may lead to acute liver failure (ALF). Perturbations of intestinal microbiota are related to severe liver disease. To study the correlations between faecal microbiota and the occurrence and exacerbation of hepatitis E virus (HEV) infection, we characterized 24 faecal samples from 12 patients with acute hepatitis E (AHE) and 12 patients with HEV-ALF using high-throughput sequencing. We found both the alpha and beta diversity indices showed no significant differences between the AHE and HEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…This outcome indicated that HEV infection promoted the expression of ERAb, CK7, VIM, and VEGF and accelerated adverse pregnancy outcomes. The inhibition of ER-α expression by HEV infection has been confirmed in pregnant women and HEV cell cultures [16,17]. In the present study, ER-α expression was significantly suppressed in the uteruses of HEV-infected pregnant mice or mice that had experienced miscarriage.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This outcome indicated that HEV infection promoted the expression of ERAb, CK7, VIM, and VEGF and accelerated adverse pregnancy outcomes. The inhibition of ER-α expression by HEV infection has been confirmed in pregnant women and HEV cell cultures [16,17]. In the present study, ER-α expression was significantly suppressed in the uteruses of HEV-infected pregnant mice or mice that had experienced miscarriage.…”
Section: Discussionsupporting
confidence: 74%
“…The reduction in ER-α expression inhibited the phosphorylation of S6 in the PI3K-AKT-mTOR signaling pathway and subsequently increased HEV replication [18]. Our previous studies have shown that HEV infection regulates estrogen signaling pathways by inhibiting the cAMPK-PKA-CREB and PI3K-AKT-mTOR signaling pathways [17,18]. Thus, the dysregulation of genes in the uterus may be responsible for adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis E cases were defined based on positive serum anti-HEV IgM, combined with clinical presentation of acute hepatitis (e.g., elevated liver enzymes and/or jaundice and/or non-specific symptoms, such as fatigue, itching, and nausea). The following exclusion criteria were established as previously reported ( 7 ): (1) use of antibiotics during the previous month; (2) current bacterial or fungal infections; (3) co-infection with hepatitis A virus, hepatitis B virus, or hepatitis C virus, or the presence of alcoholic fatty liver disease; (4) drug-induced liver disease; (5) autoimmune liver disease; (6) liver cancer, reproductive embryonic cancer, and/or female pregnancy; (7) co-infection with cytomegalovirus or Epstein–Barr virus; (8) presence of metabolic associated fatty liver disease; (9) approval for liver transplantation; and (10) incomplete data.…”
Section: Methodsmentioning
confidence: 99%
“…The enteric viruses can interact with the gut microbiota in both direct and indirect manners, resulting in devastating effects on the gut microbial ecosystem [ 97 , 98 ]. HEV infection has been reported to increase the abundance of Lactobacillaceae and Gammaproteobacteria in the fecal samples of patients with acute liver failure [ 99 ]. In contrast, supplementation with the probiotic bacterium Enterococcus faecium NCIMB 10415 can effectively promote HEV removal in infected pigs [ 100 ].…”
Section: Interconnection Between Oral and Gut Microbiomes: Oral–gut Microbiome Axismentioning
confidence: 99%